Forest wildfire hazard analyses: A point processes approach (Publicaciones en Ciencias y Tecnología, 2017)
Point stochastic processes represent a very useful tool for the analysis of hazard factors in wildfire. In this article, the occurrence of wildfire is studied from a spatial-temporal Poisson process, in which the intensity function thereof is considered as a wildfire hazard characterization based on parametric and non-parametric techniques. Finally, it is considered a set of real data, provided by the Ministerio del Poder Popular para el Ambiente from Instituto Nacional de Meteorología e Hidrologia (INAMEH) of Venezuela, relating to widlfire produced on a particular day. The hazard functions are estimated based on the proposed model and wildfire hazard maps are generated, which are adjusted to the geographical and climatic characteristics of the country.
Keywords: point process; non-parametrics methods; non-homogeneus poisson process